Disease Activity and Health-related Quality of Life Relationships with Work Productivity in Patients with Ulcerative Colitis in OCTAVE Induction 1 and 2 and OCTAVE Sustain. (22nd October 2022) - Targownik, Laura; Dubinsky, Marla C; Steinwurz, Flavio; Bushmakin, Andrew G; Cappelleri, Joseph C; Tai, Elaine; Gardiner, Sean; Hur, Peter; Panés, Julian
Abstract: Background: Tofacitinib is an oral small molecule Janus kinase inhibitor for the treatment of ulcerative colitis [UC]. We evaluated the relationship between Mayo/Inflammatory Bowel Disease Questionnaire [IBDQ] scores and Work Productivity and Activity Impairment-UC [WPAI-UC] components in patients with UC. Methods: All available pooled data from three Phase 3 tofacitinib studies [OCTAVE Induction 1 and 2 and OCTAVE Sustain] were included. Relationships were estimated using repeated measures regression models with Mayo score/subscores or IBDQ total/domain scores as a separate anchor predictor and WPAI-UC components as the outcome. Results: Evidence for linear relationships was confirmed between Mayo/IBDQ scores and WPAI-UC components. Robust relationships between total Mayo score/IBDQ total score and WPAI-UC presenteeism, work productivity loss, and activity impairment were observed; relationships with absenteeism were weak. Total Mayo scores of 0 and 12 corresponded, on average, to WPAI-UC component scores of < 15% and ≥ 60%, respectively, and IBDQ total scores of 224 and 32 corresponded, on average, to WPAI-UC component scores of < 6% and ≥ 90%, respectively. Presenteeism, work productivity loss, and activity impairment [all 0–100%], respectively, improved on average by 14.7, 13.6, and 16.4 percentage points for every 3-point improvement in total Mayo score, and by 8.1, 7.9, and 8.8 percentage points for every 16-point improvement in IBDQ total score. Conclusion: Robust relationships between Mayo/IBDQ scores with WPAI-UC presenteeism, work productivity loss, and activity impairment suggest that patient productivity and non-work activities are strongly associated with disease activity and HRQoL. The weak relationships with absenteeism suggest that patients attend work regardless of their disease activity/poor HRQoL. ClinicalTrials.gov: NCT01465763;NCT01458951;NCT01458574. Graphical Abstract: